Inferring natural selection signals in Plasmodium vivax-encoded proteins having a potential role in merozoite invasion (2015)
Detecting natural selection signals in Plasmodium parasites antigens might be used for identifying potential new vaccine candidates. Fifty-nine Plasmodium vivax-Sal-I genes encoding proteins having a potential role in invasion were used as query for identifying them in recent P. vivax strain genome sequences and two closely-related Plasmodium species. Several measures of DNA sequence variation were then calculated and selection signatures were detected by using different approaches. Our results may be used for determining which genes expressed during P. vivax merozoite stage could be prioritised for further population genetics or functional studies for designing a P. vivax vaccine which would avoid allele-specific immune responses. © 2015 Elsevier B.V.